2018
DOI: 10.1002/jgh3.12045
|View full text |Cite
|
Sign up to set email alerts
|

Risk of small intestinal bacterial overgrowth in patients receiving proton pump inhibitors versus proton pump inhibitors plus prokinetics

Abstract: Background and AimIntestinal dysmotility is considered a risk factor for small intestinal bacterial overgrowth (SIBO). Prokinetics improve intestinal motility and are often prescribed with proton pump inhibitors (PPIs) in patients with gastroesophageal reflux disease (GERD) and/or functional dyspepsia. The present study aimed to evaluate the prevalence of SIBO and the orocecal transit time (OCTT) in patients taking PPI compared with those taking PPI plus prokinetics.MethodsThe study is a single‐center, cross‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
1
16
0
3
Order By: Relevance
“…A more recent paper found that the use of prokinetics in patients on PPIs may reduce the risk of SIBO, by enhancing intestinal motility. 61 A very interesting Italian study 62 showed that while patients with nonerosive reflux disease who received PPIs for typical reflux-related symptoms obtained relief from heartburn and regurgitation, they complained of new onset, SIBO-related, bowel symptoms, whose incidence increased over time. Glucose hydrogen breath test was found positive in 11/42 (26%) subjects and-by a post hoc analysis-a significant (P < 0.05) percentage of patients (8/42) met the Rome III criteria for IBS.…”
Section: Clinical Consequences Of Ppi-induced Changes In Intestinal Mmentioning
confidence: 99%
“…A more recent paper found that the use of prokinetics in patients on PPIs may reduce the risk of SIBO, by enhancing intestinal motility. 61 A very interesting Italian study 62 showed that while patients with nonerosive reflux disease who received PPIs for typical reflux-related symptoms obtained relief from heartburn and regurgitation, they complained of new onset, SIBO-related, bowel symptoms, whose incidence increased over time. Glucose hydrogen breath test was found positive in 11/42 (26%) subjects and-by a post hoc analysis-a significant (P < 0.05) percentage of patients (8/42) met the Rome III criteria for IBS.…”
Section: Clinical Consequences Of Ppi-induced Changes In Intestinal Mmentioning
confidence: 99%
“…The notion that a slowed intestinal transit may predispose to SIBO is supported by two recent studies in adults (90, 91). In the most recent study, by Revaiah et al (90), two patient groups (i.e., PPI-group and PPI + prokinetic group) underwent a GHBT and lactulose hydrogen breath test (LHBT) and orocecal transit time assessment. Interestingly, SIBO was documented more frequently in the PPI alone group than in the PPI + prokinetic group, and SIBO-positive patients had slower orocecal transit times than SIBO-negative patients.…”
Section: Risk Factors For Sibomentioning
confidence: 86%
“…The second possible mechanism is related to intestinal bacterial overgrowth and translocation. PPIs, as acid suppressors, are known to induce intestinal dysbiosis and subsequent development of small intestinal bacterial overgrowth [25][26][27]. The complication of small intestinal bacterial overgrowth is more problematic among patients with cirrhosis than in healthy individuals, as they tend to have some degree of immunodeficiency through several mechanisms, including loss of Kupffer in the hepatic reticuloendothelial system, imbalance of cytokines causing immune cell dysfunction, and decreased hepatic synthesis of complements and acute phase reactants [4,11,28,29].…”
Section: Discussionmentioning
confidence: 99%